Decision-Making Styles of School Heads and Their Perceived Work Performance of Teachers in Public Elementary Schools - Raymund Delmonte , Capacite (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
This study correlated selected elementary school heads’ decision-making styles and their perceived work performance among their teachers in the division of Eastern Samar during the school year 2020–2021. An electronic two-part survey questionnaire generated by Google was utilized in collecting the data, which were analyzed via median, interquartile range, and Spearman's rho test of significant relationship at 0.05 level of significance. The findings revealed that the majority of elementary school principals frequently use dependent decision-making styles, while their teachers perform the expected seven key result areas the majority of the time. Moreover, a strong and positive relationship was established between the dependent decision-making style of school heads and their teachers’ work performance. It can be deduced that good decision-making among school leaders has a direct impact on the overall performance of their teaching force. Hence, the researcher recommends extending this investigation to secondary school heads to further validate the findings.